The Relationship Between Length of Work and Use of Personal Protective Equipment on the Incidence of Contact Dermatitis in Seaweed Farmers in Bungin Permai Village, South Konawe Regency - Kuswary, Niken (Waluya The International Science of Health Journal, 2025)
Introduction: Seaweed farmers are people who cultivate seaweed, from seeding and maintenance to harvesting, which is then sold. These seaweed farmers are highly susceptible to occupational diseases. Occupational diseases are diseases related to work activities. Contact dermatitis is one of the occupational diseases frequently suffered by seaweed farmers in Bungin Permai Village, South Konawe Regency. The purpose of this study was to determine the relationship between length of service and the use of personal protective equipment with the incidence of contact dermatitis among seaweed farmers in Bungin Permai Village, South Konawe Regency. Method: Research Type a quantitative with Cross Sectional Study. The sample in this study was 175 seaweed farmers in Bungin Permai village taken using proportional simple random sampling technique with the Chi-Square Test. Result: Based on the Chi-Square test, it shows that there is a relationship between length of work and the incidence of contact dermatitis in seaweed farmers with a p-value of 0.000, there is a relationship between the use of personal protective equipment and the incidence of contact dermatitis in seaweed farmers with a p-value of 0.000. Conclusion: The conclusion of this research there is a relationship between length of service and the incidence of contact dermatitis among seaweed farmers and there is a relationship between the use of personal protective equipment and the incidence of contact dermatitis among seaweed farmers in Bungin Permai Village, South Konawe Regency.